Enhancing dentin bonding quality through Acetone wet-bonding technique: a promising approach - Zhao, Shikai; Zhu, Zhiyi; Yu, Jian; Yao, Chenmin; Yu, Miaoyang; Yang, Hongye; Huang, Cui (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: This paper aimed to assess the impact of the acetone wet-bonding (AWB) technique on dentin bonding and to investigate its potential underlying mechanisms. Materials and Methods: Caries-free third molars were sliced, ground, etched, water-rinsed. Then the specimens were randomly allocated to four groups according to the following pretreatments: 1. water wet-bonding (WWB); 2. ethanol wet-bonding (EWB); 3. 50% (v/v) acetone aqueous solution (50%AWB); 4. 100% acetone solution (AWB). Singlebond universal adhesive was then applied and composite buildups were constructed. The microtensile bond strength (MTBS), failure modes and interface nanoleakage were respectively evaluated after 24 h of water storage, 10,000 times of thermocycling or one-month collagenase ageing. In situ zymography and contact angle were also investigated. Results: Acetone pretreatment preserved MTBS after thermocycling or collagenase ageing (p < 0.05) without affecting the immediate MTBS (p > 0.05). Furthermore, AWB group manifested fewer nanoleakage than WWB group. More importantly, the contact angle of the dentin surfaces decreased significantly and collagenolytic activities within the hybrid layer were suppressed in AWB group.This study suggested that the AWB technique was effective in enhancing the dentin bond durability by increasing the wettability of dentin surface to dental adhesives, removing residual water in the hybrid layer, improving the penetration of adhesive monomer, and inhibiting the collagenolytic activities. Clinical significance: The lifespan of adhesive restorations would be increased by utilization of acetone wet-bonding technique.